Enzymatic activity of precursors of Bacillus megaterium spore protease. - Hackett, R H (1983)
The protease that initiates rapid proteolysis during germination of Bacillus megaterium spores is synthesized during sporulation as a 46,000-molecular-weight polypeptide (P46) and is processed later in sporulation to a 41,000-molecular-weight polypeptide (P41), which is converted to a 40,000-molecular-weight polypeptide (P40) early in spore germination. P40 is known to be both tetrameric and enzymatically active. In this work, we show that P46 and P41 are both tetrameric, but that only P41 is enzymatically active. The identification of a zymogen form (P46) of this protease explains in part the regulation of the activity of this enzyme.